Blinding Bilateral Hyperviscosity Retinopathy in a 43-Year-Old Nigerian Male with Lymphoplasmacytic Lymphoma: A Case Report and Management Challenges - Abdulkabir A. Ayanniyi; Uchenna Godswill Ejikeme; Yohanna Tanko; Rilwan C. Muhammad; Obiageli E. Nnodu (Case Reports in Oncological Medicine)
Lymphoplasmacytic lymphomas are rare and may present with uncommon and devastating symptoms. We report a case of a 43-year-old male who presented with bleeding gums and sudden onset of bilateral blindness but was not on anticoagulants and had no family history of bleeding disorder. He had bilateral hyperpigmented infraorbital skin lesions, visual acuities (VA) of hand motion in both eyes (blindness), round and sluggish pupils, and bilateral diffuse and extensive retinal haemorrhages obliterating the retinal details with central visual field defects. The optical coherence tomography revealed retinal haemorrhage, oedema, detachment, and diffuse photoreceptors damage. Investigations revealed elevated ESR and β2 microglobulin, monoclonal peak on serum protein electrophoresis, high IG with lambda restriction on serum, and urine immunofixation with increased lymphocytes and plasma cells in the bone marrow. A diagnosis of lymphoplasmacytic lymphoma complicated by blinding hyperviscosity retinopathy was made. In the absence of an aphaeresis machine, he received four cycles of manual exchange blood transfusion (EBT) and commenced with chlorambucil/prednisolone due to difficulty in obtaining blood for continued EBT. His general condition and VA has improved and he is stable for more than six months into treatment.